2023
DOI: 10.3389/fpls.2023.1276918
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi enhance active ingredients of medicinal plants: a quantitative analysis

Ming-Li Yuan,
Meng-Han Zhang,
Zhao-Yong Shi
et al.

Abstract: Medicinal plants are invaluable resources for mankind and play a crucial role in combating diseases. Arbuscular mycorrhizal fungi (AMF) are widely recognized for enhancing the production of medicinal active ingredients in medicinal plants. However, there is still a lack of comprehensive understanding regarding the quantitative effects of AMF on the accumulation of medicinal active ingredients. Here we conducted a comprehensive global analysis using 233 paired observations to investigate the impact of AMF inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…AMF are a class of ancient fungi that can form a mutualistic symbiosis with over 80% of plant species roots in natural and agricultural systems and are mainly classified as Glomeromycota, including Diversisporales, Archaeosporales, Glomerales and Paraglomerales ( Camargo-Ricalde, 2002 ; Malar et al., 2022 ; Fan et al., 2023 ). Increasing evidence has shown that AMF play key roles in the growth and accumulation of secondary metabolites in medicinal plants ( Kumar et al., 2021 ; Ran et al., 2022 ; Zhao et al., 2022 ; Yuan et al., 2023 ; Cao et al., 2023b ). The contents of many active substances increased under the inoculation of AMF, e.g., artemisinin from Artemisia annua L ( Mandal et al., 2015 ; Domokos et al., 2018 ), glycyrrhizin and liquiritin from Glycyrrhiza uralensis Fisch ( Xie et al., 2018 , 2019 ), aloe emodin from Polygonum cuspidatum Sieb.…”
Section: Introductionmentioning
confidence: 99%
“…AMF are a class of ancient fungi that can form a mutualistic symbiosis with over 80% of plant species roots in natural and agricultural systems and are mainly classified as Glomeromycota, including Diversisporales, Archaeosporales, Glomerales and Paraglomerales ( Camargo-Ricalde, 2002 ; Malar et al., 2022 ; Fan et al., 2023 ). Increasing evidence has shown that AMF play key roles in the growth and accumulation of secondary metabolites in medicinal plants ( Kumar et al., 2021 ; Ran et al., 2022 ; Zhao et al., 2022 ; Yuan et al., 2023 ; Cao et al., 2023b ). The contents of many active substances increased under the inoculation of AMF, e.g., artemisinin from Artemisia annua L ( Mandal et al., 2015 ; Domokos et al., 2018 ), glycyrrhizin and liquiritin from Glycyrrhiza uralensis Fisch ( Xie et al., 2018 , 2019 ), aloe emodin from Polygonum cuspidatum Sieb.…”
Section: Introductionmentioning
confidence: 99%
“…The crucial role of arbuscular mycorrhizal fungi (AMF) associations in plant nutrient uptake has been widely recognized for a long time. The advantageous symbiotic relationships between plants and AMF can exert substantial influence on plant health and productivity [1,2]. While there has been significant research on the benefits of AMF for plant nutrition and growth, the impact they may have on plant disease resistance is a relatively new field of investigation.…”
Section: Introductionmentioning
confidence: 99%